Dengue and chikungunya seroprevalence among Qatari nationals and immigrants residing in Qatar - Humphrey, John M. (PLoS One, 2019)
The objective of this study is to characterize the seroprevalence of anti-dengue (DENV) and anti-chikungunya (CHIKV) antibodies among blood donors residing in Qatar who are Middle East and North Africa (MENA) nationals and non-nationals. Sera were collected from adult blood donors in Qatar from 2013 to 2016 and tested for anti-DENV and anti-CHIKV IgG using commercial microplate enzyme-linked immunosorbent assays. Age-specific seroprevalence was summarized by region/nationality: Asia (India, Philippines), Middle East (Iran, Jordan, Lebanon, Pakistan, Palestine, Syria, Yemen), North Africa (Egypt, Sudan), Qatar. The adjusted odds of anti-DENV and anti-CHIKV IgG seropositivity was estimated by logistic regression. Among 1,992 serum samples tested, Asian nationals had higher adjusted odds of being seropositive for anti-DENV antibodies compared to nationals of the Middle East (aOR 0.05, 95% CI 0.04–0.07), North Africa (aOR 0.14, 95% CI 0.10–0.20), and Qatar (aOR 0.01, 95% CI 0.01–0.03). Asian nationals also had higher adjusted odds of being seropositive for anti-CHIKV antibodies compared to those from the Middle East (aOR 0.14, 95% CI 0.07–0.27), North Africa (aOR 0.50, 95% CI 0.26–0.96), and Qatar (aOR 0.38, 95% CI 0.15–0.96). The adjusted odds of being anti-DENV seropositive was higher among anti-CHIKV seropositive adults, and vice versa (aOR 1.94, 95% CI 1.09–3.44), suggesting co-circulation of these viruses. DENV and CHIKV exposure is lower in Qatar and MENA nationals compared to Asian nationals suggesting a lower burden of DENV and CHIKV disease in the MENA. Antibodies to both viruses were detected in nationals from most MENA countries, supporting the need to better understand the regional epidemiology of these viruses.